Comparative assessment of sun/shade and oven drying on structural integrity, chemical composition and functional quality of Ziziphus jujuba Mill. fruits - Karan, Halil; Ozgen, Inanc; Aydogmus, Ercan; Arslanoglu, Hasan (Wiley, 2026)
BACKGROUND This study investigates the effects of three different drying methods - sun drying, shade drying and oven drying at 55 degrees C. Some physical, structural and chemical properties of Ziziphus jujuba Mill. fruit before and after drying are evaluated. Freshly harvested jujube fruits from the Elaz & imath;& gbreve; (Turkey) region are subjected to each drying method, and changes in surface hardness, moisture content and internal structure are analyzed. Shore A hardness measurements indicate a significant increase in fruit firmness over time, with oven-dried samples showing the highest values, followed by sun-dried samples.RESULTS Fourier transform infrared spectroscopy reveals marked chemical transformations during drying, including reductions in O-H stretching bands and shifts in C=O and C-H regions, reflecting moisture loss and modifications in sugars and polysaccharides. Weight loss calculations determine that approximately 60-65 wt% of initial mass is lost to reach a final moisture content of around 16-18 wt%. These structural and chemical changes influence the fruit's texture, rehydration ability and consumer acceptability. Drying kinetic modeling using two-term models for both oven and sun/shade drying demonstrates excellent fit (R2 = 0.9995), with oven drying showing a higher effective diffusion coefficient (Deff = 4.57 x 10-10 m2 s-1) than sun/shade drying (Deff = 7.96 x 10-11 m2 s-1), indicating more efficient moisture transport.CONCLUSION Response surface methodology is employed to optimize drying conditions and evaluate mass loss over time. (c) 2026 Society of Chemical Industry.
Keywords: Ziziphus jujuba; sun/shade drying; oven drying; effective diffusion coefficient; drying kinetics; response surface methodology